[OP.4C.07] LOADED SLOW BREATHING TRAINING REDUCES HOME RESTING BLOOD PRESSURE IN OLDER PATIENTS WITH ISOLATED SYSTOLIC HYOPERTENSION. (September 2016) - Jones, C.; Sangthong, B.; Pachirat, O.; Jones, D.
Abstract : Objective: To determine whether slow loaded breathing training can enhances blood pressure reduction associated with conventional medication. Design and method: Randomised controlled trial Thirty patients (66 ± 4 years) with isolated systolic hypertension and managed with conventional medication, were randomized into loaded breathing (LB: 6 breaths/min, 18 cm H2O), unloaded breathing (ULB: 6 breaths/min, no load) or control (C: normal breathing) groups. After a 2 week run-in, LB and ULB groups trained at home for 30 min every day for 8 weeks. Home blood pressure and heart rate measurements were taken daily in the morning throughout the study. At the end of training all patients reverted to normal breathing and home blood pressure and heart rate data continued to be recorded for a further 8 weeks. Results: After 8 weeks training, systolic blood pressure was significantly reduced by 18 ± 7 and 11 ± 4 mmHg for LB and ULB, respectively (p < 0.043), compared with the pre-training run-in period. There were no changes in the Control group. After the end of training, systolic blood pressure remained below pre-training levels for a further 6 weeks for the LB group but remained low for only one week with the ULB group. There was a small reduction in diastolic pressure with training and pulse pressures were reduced by 11 ± 5 and 5 ± 6 mmHg for LB and ULB, respectively (p < 0.01). Conclusions: It is concluded that slow breathing training, especially with an inspiratory load, is very well tolerated and could be a valuable adjunct in the management isolated systolic hypertension.